2009
DOI: 10.1128/ec.00078-09
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics of Adhesion, Invasion, and Mycelial Formation in Schizosaccharomyces pombe

Abstract: Investigation into the switch between single-celled and filamentous forms of fungi may provide insights into cell polarity, differentiation, and fungal pathogenicity. At the molecular level, much of this investigation has fallen on two closely related budding yeasts, Candida albicans and Saccharomyces cerevisiae. Recently, the much more distant fission yeast Schizosaccharomyces pombe was shown to form invasive filaments after nitrogen limitation (E. Amoah-Buahin, N. Bone, and J. Armstrong, Eukaryot. Cell 4:128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 34 publications
1
37
0
1
Order By: Relevance
“…The tea2⌬ strain did not show invasive growth after 20 days of incubation; however, a tea2⌬ strain can grow invasively after prolonged incubation (Fig. 6C) (19) . Double mutants carrying mal3⌬, tea1⌬, tea2⌬, peg1-1 H397A mutant strain ( Fig.…”
Section: Downloaded Frommentioning
confidence: 91%
See 2 more Smart Citations
“…The tea2⌬ strain did not show invasive growth after 20 days of incubation; however, a tea2⌬ strain can grow invasively after prolonged incubation (Fig. 6C) (19) . Double mutants carrying mal3⌬, tea1⌬, tea2⌬, peg1-1 H397A mutant strain ( Fig.…”
Section: Downloaded Frommentioning
confidence: 91%
“…Filamentous invasive growth has been described for S. pombe (1,19,61), but we have analyzed for the first time the growth pattern of such cells. Invasive growth of wild-type and asp1 H397A cells is a variation on the same theme that is a combination of different properties, such as cell-cell and cell-substrate adhesion, defects in cell separation, the ability to alter cell shape in response to environmental constraints, and an alteration of the normal growth pattern.…”
Section: Upstream Regulators Of Asp1 Kinase Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that gsf2 ϩ , encoding a flocculin that binds to galactose residues located on cell surface glycoconjugates, is essential not only for nonsexual flocculation but also for filamentous invasive growth in S. pombe (7,20). Cell surface glycoproteins play a key role in flocculation and filamentous invasive growth in yeasts.…”
mentioning
confidence: 99%
“…However, we found that it could be induced to invade the medium, forming elaborate elongated and branching structures very different from the well-known growth pattern (1). Invasion requires high cell density and can be encouraged by a combination of low nitrogen levels and abundant carbon (1,5). We identified several genes necessary for different stages of the process (5), while the nutritional effect requires the cyclic AMP signaling pathway (1).…”
mentioning
confidence: 88%